One step forward and two steps back in teaching an endangered language? Revisiting L2 reading in Irish. Issue 3 (1st September 2016) - Hickey, Tina M.; Stenson, Nancy
ABSTRACT: Hickey's (1991) article [Leisure reading in a second language: An experiment with audio tapes. Language, Culture and Curriculum, 4 (2), 119-131. Retrieved fromhttp://dx.doi.org/10.1080/07908319109525098 ] reported the benefits of audio-support for L2 reading of real books, showing gains in fluency and motivation among 9-year-old learners of Irish. In the 25 years since that, there have been significant changes in the educational and sociolinguistic context in which Irish and Irish reading are taught. That period encompassed a major shift in the curricular approach to teaching Irish, and changes in status. With the advent of a new primary school curriculum, it is time to revisit this topic and reflect on how changes in the interim have impacted on the teaching of L2 Irish reading. This article reviews the societal and educational changes relevant to teaching Irish in mainstream (English-medium) schools, offering insights into current practices from a qualitative study of teachers' reflections on their pedagogical strategies, perceived priorities and difficulties encountered. Finally, it considers the advances made in the provision of materials supporting L2 Irish reading in the intervening years, and the challenges that remain with regard to promoting the use of those materials in mainstream classrooms.